Study of Coffee Crops Development in Rantau Pulut Village, Seruyan Regency Central Kalimantan - Wahdah, Rabiatul; Taher, Ratnah; Syarbini, Muhammad; Wilda, Kamilia; Haris, Abdul (UNIVERSITY OF LAMPUNG, 2023)
Coffee is one of Indonesia’s most prominent agricultural commodities; various coffee plants are produced with the best results from the west to the east of Indonesia. Indonesia’s climate and geographical location are suitable for cultivating the coffee plant. This study aims to determine the level of land suitability and the limiting factors for the development of coffee plants, as well as provide direction/recommendations in the development of coffee plants in Rantau Pulut Village, Seruyan Regency, Central Kalimantan. Land suitability has the potential to be increased from S2 to S1 by managing the limiting factors for the number of dry months and rainfall, SB (Saturated Base), pH, P2O5, and K2O so that the potential land suitability for the study area is S2r. The method used in this study is a qualitative descriptive survey method with a matching system, namely matching land quality/land characteristics with land use requirements for agricultural commodities to be developed. The result of the actual land suitability analysis of Rantau Pulut Village for developing robusta coffee plants is S3fn